Development of management skills for entrepreneurship in venezuelan migrants with a vocation of residence in Santiago de Cali - Delgado Salazar, Adriana Jineth; Cháves Manzano, Haydn Rodrigo (SATHIRI, 2020)
In recent years, Venezuelan migration to Colombia has prompted that government and institutions to analyze how to deal this problem, through the generation of alternatives that allow this population to have a better quality of life in the country. Migrants has been in need of to resort to empirical ventures based on their knowledge and culture, to satisfy their unsatisfied basic needs. It was important to determine that the migrants had a vocation of residence in Santiago de Cali, a condition that facilitated accompaniment and orientation process. This research was developed with a qualitative approach to action-research design in articulation with praxeology; it was proposed to provide the Venezuelan migrant population with basic management tools that would allow them to better guide their business ideas through a training process, for the subsequent delivery of a base capital with which they could start or strengthen their productive enterprises. In the first phase of the project, the workshops were oriented in two lines, one administrative and the other psychosocial that allowed to address the migratory grief. The second phase consisted of monitoring the productive enterprises after the delivery of the base capital, showing that the pandemic and the displacement conditions continue to be a factor of high impact.